Religious Development for Converts through the Literacy Program in Dukuh Trenceng - Tania Nur Hariani; Niken Ayu Ningtiyas; Ita Yogi Pratama; Sumaji (Jurnal Pengabdian Pancasila (JPP), 2023)
This article discusses the problems experienced by converts to Islam in Trenceng Hamlet. Many residents of Dukuh Trenceng have embraced Islam but they face many religious problems such as religious facilities and coaching. The purpose of this service is to provide guidance, strengthen religious concepts, practice worship training. As for coaching through the literacy program, there are three programs; regular studies, practical worship practices and learning to read the Al-Quran using the wafa method. This service activity also has a positive impact on the Dukuh Trenceng converts group, which can increase obedience and enthusiasm for worship.